RELEVANSI WATAK TOKOH UTAMA DALAM CERPEN SRI SUMARAH KARYA UMAR KAYAM TERHADAP NILAI KEHIDUPAN SEHARI HARI: KAJIAN FEMINISME EKSISTENSIALIS - Romlah, Siti; Izati, Isna Nur; Yunus, Syarifudin (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2025)
This study aims to examine the relevance of the main character's traits in the short story Sri Sumarah by Umar Kayam to the values of everyday life, particularly within the framework of a patriarchal culture that shapes and restricts women's roles. Utilizing Simone de Beauvoir’s existentialist feminist perspective, the study employs a qualitative descriptive method combined with content analysis to explore and interpret the character of Sri Sumarah. The findings reveal that women are often idealized for their sacrifices, which, in reality, are manifestations of gender inequality and the suppression of individual autonomy. Female identity is constructed through social norms dictated by patriarchal structures. The characterization of Sri Sumarah is profoundly relevant to contemporary life, especially in relation to modern women who are increasingly expected to demonstrate independence and psychological resilience. Despite societal and cultural limitations, she retains the freedom to make decisions that shape her life. Her determination and ability to endure in challenging situations demonstrate that women can define the meaning of their own lives without depending on societal recognition or patriarchal definitions. The values presented in Sri Sumarah, such as patience, sincerity, perseverance, and self-reliance, can inspire contemporary women to face life’s challenges with greater strength and independence. Thus, this short story not only teaches moral values but also offers a new perspective on understanding women's struggles within broader social and cultural contexts.